Microbiological risk factors, ICU survival, and 1-year survival in hematological patients with pneumonia requiring invasive mechanical ventilation - Benjamin Seybold; Timo Funk; Peter Dreger; Gerlinde Egerer; Juliane Brandt; Carsten Mueller-Tidow; Nicola Giesen; Uta Merle (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose To identify pathogenic microorganisms and microbiological risk factors causing high morbidity and mortality in immunocompromised patients requiring invasive mechanical ventilation due to pneumonia. Methods A retrospective single-center study was performed at the intensive care unit (ICU) of the Department of Internal Medicine at Heidelberg University Hospital (Germany) including 246 consecutive patients with hematological malignancies requiring invasive mechanical ventilation due to pneumonia from 08/2004 to 07/2016. Microbiological and radiological data were collected and statistically analyzed for risk factors for ICU and 1-year mortality. Results ICU and 1-year mortality were 63.0% (155/246) and 81.0% (196/242), respectively. Pneumonia causing pathogens were identified in 143 (58.1%) patients, multimicrobial infections were present in 51 (20.7%) patients. Fungal, bacterial and viral pathogens were detected in 89 (36.2%), 55 (22.4%) and 41 (16.7%) patients, respectively. Human herpesviruses were concomitantly reactivated in 85 (34.6%) patients. As significant microbiological risk factors for ICU mortality probable invasive Aspergillus disease with positive serum-Galactomannan (odds ratio 3.1 (1.2-8.0), p = 0.021,) and pulmonary Cytomegalovirus reactivation at intubation (odds ratio 5.3 (1.1–26.8), p = 0.043,) were identified. 1-year mortality was not significantly associated with type of infection. Of interest, 19 patients had infections with various respiratory viruses and Aspergillus spp. superinfections and experienced high ICU and 1-year mortality of 78.9% (15/19) and 89.5% (17/19), respectively. Conclusions Patients with hematological malignancies requiring invasive mechanical ventilation due to pneumonia showed high ICU and 1-year mortality. Pulmonary Aspergillosis and pulmonary reactivation of Cytomegalovirus at intubation were significantly associated with negative outcome.

Metallothionein is elevated in liver and duodenum of Atp7b(−/−) mice - Chengcheng Christine Zhang; Martin Volkmann; Sabine Tuma; Wolfgang Stremmel; Uta Merle (BioMetals, 2018)

Localization of the iron-regulatory proteins hemojuvelin and transferrin receptor 2 to the basolateral membrane domain of hepatocytes - Uta Merle; Franziska Theilig; Evelyn Fein; Sven Gehrke; Birgit Kallinowski; Hans-Dieter Riedel; Sebastian Bachmann; Wolfgang Stremmel; Hasan Kulaksiz (Histochemistry and Cell Biology, 2007)